SIFAT DAN KARAKTER TOKOH UTAMA PEREMPUAN DALAM PERSPEKTIF HEGEMONI IDEOLOGI PATRIARKI PADA NOVEL RONGGENG DUKUH PARUK KARYA AHMAD TOHARI - Novi Andari; Anik Cahyaning Rahayu; Sudarwati Sudarwati (Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract. This article discusses the hegemony of patriachry on woman in Tohary’s novel entitled Ronggeng Dukuh Paruk. The discussion is around Javanese women’s adversity because of patriachal ideology built by men. A descriptive qualitative method was applied to approach the matter. The result shows that being the ronggeng dancers meant that the women’ lives were under men occupation. The women were under the hegemony of men ideology, but the women, being Javanese, had to receive their conditions. It also shows that Srintil, the main character, was described as patient, obedience, willing to sacrifice, and suffering person. Key words: hegemoni Gramsci, ideologi patriarki, wanita Jawa, analisis tokoh